Urgensi Pelatihan Syukur (Gratitude Traning) untuk Meningkatkan Subjective Well-Being â€œIbu Mudaâ€ dalam Konteks Keluarga - Prastuti, Endang (Universitas Muhammadiyah Jember, 2020)
Building a family life is basically aimed to successfully achieving life satisfaction and happiness, which we use the term subjective well-being. Empirical data shows that family life is a dynamic process of adaptation, therefore events such as problems, stress, pressure and crisis are not determinants of subjective well-being, but rather how to improve the ability of individuals to make the intended coping. Gratitude is a form of coping response which is a predictor of subjective well-being. Gratitude can be activated and trained continuously through the process of learning and training throughout life, thus forming the power of transcendence. The research findings show that: gratitude can be done by implementing cognitive emotional regulation strategies, namely (a) refocus on planning, (b) putting into perspective, (c) positive appraisal. In addition, the activation of gratitude can be done through mindfulness by using the strategy 3 A, namely (a) Attention (b) Awareness (c) Acceptance, and activating gratitude with the counting of blessing method. Recommendations for future research: it is necessary to develop a gratitude training model that is proven effective in increasing the subjective well-being of